Marine products for healthcare : functional and bioactive nutraceutical compounds from the ocean - Venugopal, V. [ (Vazhiyil)] , 1942- (Boca Raton, FL : CRC Press/Taylor & Francis, 2009)
Discusses the importance of marine products as a source of nutraceuticals, food additives, and other useful ingredients in health protection and product formulation. This book presents the functional properties of various macromolecules available from seafood and other marine resources such as seaweed and coral reef.
1. Functional foods : an overview -- Marine habitat and resources -- Seafood proteins : functional properties and protein supplements -- Seafood proteins : nutritional value, bioactive peptides, marine and cold-adapted enzymes -- Polyunsaturated fatty acids and their therapeutic functions -- Seafood processing wastes: chitin, chitosan, and other compounds -- Cartotenoids -- Marine sources of vitamins and minerals -- Seaweed : nutritional value, bioactive properties, and uses -- Seaweed hydrocolloids -- Marine microalgae, other microorganisms, and corals -- Drugs and pharmaceuticals from marine sources -- Marine nutraceuticals for food fortification and enrichment -- Marine macromolecules as nutraceutical carriers and biofilms -- Safety hazards with marine products and their control
Includes bibliographical references and index
Keywords: Functional foods; Marine pharmacology; Seafood -- Health aspects